PENGARUH INTERNET FINANCIAL REPORTING, KETEPATAN WAKTU PENYAMPAIAN INFORMASI KEUANGAN WEBSITE, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP ABNORMAL RETURN (Studi Empiri spada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2012-2014) - Dita Amelia; Linda Linda (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The research examines the effect ofinternet financial reporting, timeliness submission of financial information website, firm size, and profitability on abnormal return of mining company listed in Indonesia Stock Exchange in 2012-2014.Secondary data were sourced from the financial statements, published by the capital market reference center at the Indonesia Stock Exchange and list of daily stock price in Yahoo Finance. The research type used in this research is hypothesis testing, by using simple random sampling method. There are 90 samples of the data that become the object to be researched. This research uses multiple linear regression analysis to test the hypothesis.The results of this research show that simultaneous of internet financial reporting, timeliness submission of financial information website, firm size, and profitability have effect on abnormal return. Partially the research shows that (1) internet financial reporting have positive effect on abnormal return, (2) timeliness submission of financial information website have positive effect on abnormal return, (3) firm size have positive effect on abnormal return, and (4) profitability have no effect on abnormal return. Keywords: Internet Financial Reporting, Timeliness Submission Of Financial Information Website, Firm Size, Profitability, Abnormal Return.